Human resource development in learning organization - Kumpikaitė, Vilmantė (Journal of Business Economics and Management, 2008)
This paper draws on prior exploration on human resource development in a learning organization, including theories about a learning organization, its features, human resource development and learning styles in organizations. The main aim of this paper is to explore human resource development and learning styles in organizations. The author introduces results of the survey covering 37 Lithuanian organizations selected from various industries ranging from a newspaper and transportation, insurance and radio station, to those in trade and manure production. The research shows that mostly explored organizations have a formalized approach to learning and has only a few features of a learning organization.First published online: 14 Oct 2010